Acerca de los "Comentarii Familiares" de Jodoco Badio al "Ars poetica" de Horacio y a las "Saturae" de Persio - Martínez Sobrino, Alejandro (2017)
The Commentarii Familiares by Jodocus Badius Ascensius retain quite a traditional disposition. At first, they were completed to support the teaching of the Latin language, and after, before being printing-pressed, they were renewed with the explanations of alienexegesis. This renovation makes his explanations show unique characteristics, to the point that sometimes even the reprinting of his explanations to a same work do not allow them to be qualified as reedition. Nevertheless the obvious traditional disposition possessed by the Commentarii Familiares is consistent with that retained by the French poetry at least up to the second half of the sixteenth century.
Keywords: Horacio Flaco, Quinto; Persio Flaco, Aulo; Crítica textual